Unlocking The Potential Of Nursing Teams: A Systematic Review Of Training And Development Programs In Saudi Healthcare (The Review of Diabetic Studies, 2025)
Background: Nursing workforce is very important in providing the effective treatment to patients in the healthcare centers. Training and development program is effective in enhancing the nursing competency and skills.Objective:  The objective of this research is to systematically review the literature to unlock the potential of nursing teams with respect of training and development programs in Saudi Healthcare.Method: With an emphasis on studies published between 2021 and 2025, research was categorized using databases such as Scopus, PsycINFO, Google Scholar and Web of Science. The analysis specifically examined the training and development of nursing team in Saudi Healthcare, a total of 17 papers were included in the systematic review.Result: Four themes were extracted from the SR. These following themes are as Nursing Competency Development; Nursing Training & Developing New Skill; Female Nursing Empowerment & Future Training & Development Challenges.Conclusion: The systematic review of Unlocking the Potential of Nursing Teams concerning Training and Development Programs in Saudi Healthcare found limitations and suggested improvements. KSA is developing nursing team training programs due to a lack of literature. The studies were limited and local. Research on training doesn't explain it. What development programs are underway. Unpublished research in local publications should be examined. Some studies use self-reported data. Gender-related training and development impediments were limited. The education competency and development framework, gender dynamics, cultural barriers, and retention variables should be studied longitudinally and experimentally. This article explores Saudi Healthcare's training and development strategies to unleash nursing teams' potential in workforce, competency, and new skills to better serve patients and domain specialists.